2020
DOI: 10.1021/acs.jchemed.0c00687
|View full text |Cite
|
Sign up to set email alerts
|

An Applied Research-Based Approach to Support Chemistry Teachers during the COVID-19 Pandemic

Abstract: In this Communication paper we describe how a research-based approach was applied in Israel to support high-school chemistry teachers, who continued to teach using technology during the COVID-19 pandemic. Within the TPACK (technological pedagogical content knowledge) framework for teachers’ knowledge in technological environments, we developed a questionnaire for chemistry teachers, with the goal to reveal the difficulties they encountered, their needs, and their means for sharing their knowledge, materials, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 17 publications
1
34
0
3
Order By: Relevance
“…In a Vietnamese study, Tran et al (2020) found that students who were intrinsically motivated and believed that "self-learning was necessary because it maintained their learning habits" (p. 12), studied approximately 40 minutes more a day than their classmates. However, Hodgen et al (2020) found that students who could self-regulate their learning were often highattainers, who already had those skills prior to the pandemic. Yet there were examples of students exhibiting greater ownership of their learning and developing a new sense of independence during school closures (e.g., Chiu, 2021;Hira & Anderson, 2021).…”
Section: Cognitive Engagementmentioning
confidence: 99%
See 3 more Smart Citations
“…In a Vietnamese study, Tran et al (2020) found that students who were intrinsically motivated and believed that "self-learning was necessary because it maintained their learning habits" (p. 12), studied approximately 40 minutes more a day than their classmates. However, Hodgen et al (2020) found that students who could self-regulate their learning were often highattainers, who already had those skills prior to the pandemic. Yet there were examples of students exhibiting greater ownership of their learning and developing a new sense of independence during school closures (e.g., Chiu, 2021;Hira & Anderson, 2021).…”
Section: Cognitive Engagementmentioning
confidence: 99%
“…Parents also assisted with creating the videos, which enhanced the experience greatly for students. In a study by Langansan (2020), social media helped break down barriers between teachers, students and parents, as the teacher created Facebook groups for each class, creating announcements of work due and had group chats for teachers and parents to keep lines of communication open. However, despite the reported benefits of using Facebook Live for conducting synchronous lessons, adequate internet connectivity was an issue in some cases (e.g., Chirinda et al, 2021) and many teachers opted for WhatsApp 7 instead (Lawrence & Fakuade, 2021).…”
Section: The Role Of Social Networking Tools On Student Engagementmentioning
confidence: 99%
See 2 more Smart Citations
“…Así mismo, se evidenció que los docentes desconocían como asociar la pedagogía con la tecnología (Rap et al, 2020) pues bien, muchos de ellos han usado herramientas tecnológicas, se queda en aplicaciones básicas. Es por ello que proporcionar una variedad de herramientas tecnológicas especializadas en el área del conocimiento de los profesores se vuelve categórico para lograr competencias digitales (Canbazoglu Bilici et al, 2016).…”
Section: Trabajos Relacionadosunclassified